Dukcapil Service Innovation in Improving the Quality of Service in the Lebong District - Novliza Eka Patrisia; Hardi Warsono; Kismartini Kismartini; Reni Shinta Dewi (Jurnal Public Policy, 2022)
This article aims to describe and provide an overview of the application-based innovation of the Lebong Dukcapil Service in the process of making population administration documents in the Lebong Regency to improve the quality of quality public services. Registration Service as the service provider in the field of population and civil registration. This research uses descriptive qualitative research, data sources use interview techniques and direct observation in the field, as well as documentation. The results of this study indicate that population administration services through the Lebong Dukcapil Service application at the Lebong Regency Population and Civil Registration Service are quite good This is seen from the aspects: of relative advantage, suitability, complexity, possibility to try, and ease of observation. With the application-based innovation of the Lebong Dukcapil Service, it is expected to be able to improve service quality through effective and efficient service patterns, as well as being oriented towards innovation targets. possibility to try, and ease of observation. With the application-based innovation of the Lebong Dukcapil Service, it is expected to be able to improve service quality through effective and efficient service patterns, as well as being oriented towards innovation targets. possibility to try, and ease of observation. With the application-based innovation of the Lebong Dukcapil Service, it is expected to be able to improve service quality through effective and efficient service patterns, as well as being oriented towards innovation targets